Contribuição ao estudo do acionamento avançado do motor síncrono de ímãs permanentes: abordagem baseada nos modos deslizantes de ordem superior - Dias, Milena Sabrina Godoi (2009)
This work presents a study of first and second order sliding mode controllers applied to permanent magnet synchronous motor.The aim is a theoretical study and an experimental implementation, using the DSP TMS320F2812 platform, of two second order sliding mode controllers. In addiction a study about the first order sliding mode is presented. The inclusion of this topic aims to provide a comparison elements, related to the performance, precision, robustness, chattering and implementation aspects. In the beginning of this work, are presented the principal concepts related to the approach of the variable structure control. Afterwards, a theoretical study about the first order sliding mode is realized. Beyond the theoretical formulation, the chattering and some techniques for your reduction are presented. Following, two second order sliding mode controllers are presented. The final half of the work presents the application of the sliding mode controllers to the permanent magnet motor. First, the theoretical studies with simulation results are presented. Subsequently, the results in the experimental setup show the viability of the controllers applications. The controllers use the current stator measurements, classical in this kind of application, and the position rotor measurement, obtained by absolute encoder. The tests to the controllers performance analysis consider errors in the system parameters and the load torque such as perturbation input.